2020
DOI: 10.1155/2020/2837853
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Nrf2/HO‐1 Pathway by Amomum villosum Extract Suppresses LPS‐Induced Oxidative Stress In Vitro and Ex Vivo

Abstract: Despite its deleterious effects on living cells, oxidative stress plays essential roles in normal physiological processes and provides signaling molecules for cell growth, differentiation, and inflammation. Macrophages are equipped with antioxidant mechanisms to cope with intracellular ROS produced during immune response, and Nrf2 (NF-E2-related factor 2)/HO-1 (heme oxygenase-1) pathway is an attractive target due to its protective effect against ROS-induced cell damage in inflamed macrophages. We investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Previously studies show that ROS regulates changes in levels of molecules involved in mediating oxidative stress via different signaling cascades, such as the Nrf2/HO-1 signaling axis. 18,44,45 Nrf2 is a transcription factor that regulates the expression of variety of cytoprotective molecules, and HO-1 protects cells by reducing ROS. [18][19][20] Previous reports indicate that under normal physiological circumstances, Nrf2 is mainly present in the cytoplasm; however, elevated ROS levels promote its nuclear translocation and transcription of genes encoding proteins involved in controlling oxidative stress, including HO-1.…”
Section: Discussionmentioning
confidence: 99%
“…Previously studies show that ROS regulates changes in levels of molecules involved in mediating oxidative stress via different signaling cascades, such as the Nrf2/HO-1 signaling axis. 18,44,45 Nrf2 is a transcription factor that regulates the expression of variety of cytoprotective molecules, and HO-1 protects cells by reducing ROS. [18][19][20] Previous reports indicate that under normal physiological circumstances, Nrf2 is mainly present in the cytoplasm; however, elevated ROS levels promote its nuclear translocation and transcription of genes encoding proteins involved in controlling oxidative stress, including HO-1.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, inflammatory protein modifications may regulate by NF-κB during different signaling cascades, such as the nuclear factor erythroid 2-related factor (Nrf2) signaling pathway. [17][18][19][20] Nrf2 activation and absence may regulate the expression of NF-κB and pro-inflammatory cytokines. [20][21][22] Moreover, previous studies have shown that Nrf2 can protect cells by reducing inflammation through Nrf2 and heme oxygenase-1 (HO-1) pathway.…”
Section: Introductionmentioning
confidence: 99%
“…A. villosum is widely distributed in South and East Asia [ 2 ]. Accumulating studies demonstrated that the major bioactive components of A. villosum included volatile oils, flavonoids, terpenoids and polysaccharides, which showed anti-inflammation, anti-oxidant, anti-ulceration and anti-microbial activities [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%